Three-Dimensional Micro-Computed Tomography of the Adult Mouse Ovary - Fiorentino, Giulia; Parrilli, Annapaola; Garagna, Silvia; Zuccotti, Maurizio (Frontiers in Cell and Developmental Biology, 2020)
In the mouse ovary, folliculogenesis proceeds through eight main growth stages, from small primordial type 1 (T1) to fully-grown antral T8 follicle. Most of our understanding of this process was obtained with approaches that disrupted the ovary three-dimensional (3D) integrity. Micro-Computed Tomography (microCT) allows the maintenance of the organ structure and a true in-silico 3D reconstruction, with cubic voxels and isotropic resolution, giving a precise spatial mapping of its functional units. Here, we developed a robust method that, by combining an optimized contrast procedure with microCT imaging of the tiny adult mouse ovary, allowed 3D mapping and counting of follicles, from pre-antral secondary T4 (53.2+12.7 µm in diameter) to antral T8 (321.0+21.3 µm) and corpora lutea, together with the major vasculature branches. Primordial and primary follicles (T1-T3) could not be observed. Our procedure highlighted, with unprecedent details, the main functional compartments of the growing follicle: granulosa, antrum, cumulus cells, zona pellucida, and oocyte with its nucleus. The results describe a homogeneous distribution of all follicle types between the ovary dorsal and ventral regions. Also, they show that each of the eight sectors, virtually segmented along the dorsal-ventral axis, houses an equal number of each follicle type. Altogether, these data suggest that follicle recruitment is homogeneously distributed all-over the ovarian surface. This topographic reconstruction builds sound bases for modelling follicles position and, prospectively, could contribute to our understanding of folliculogenesis dynamics, not only under normal conditions, but, importantly, during ageing, in the presence of pathologies or after hormones or drugs administration.